Functional human skin explants as tools for assessing mast cell activation and inhibition - Villanueva, Clarence Rachel; Barksdale, Keane; Owolabi, Tinuola; Bridges, Donavan; Chichester, Kristin; Saini, Sarbjit; Oliver, Eric T. (Frontiers in Allergy, 2024)
Mast cells are activated through a variety of different receptors to release preformed granules and mediators synthesized de novo. However, the physiology and function of mast cells are not fully understood. Traditional studies of mast cell activation in humans have utilized cultures of tissue-derived mast cells including CD34+ progenitor cells or well-characterized commercially available cell lines. One limitation of these methods is that mast cells are no longer in a natural state. Therefore, their applicability to human skin disorders may be limited. Human skin explant models have been utilized to investigate the short-term effects of cell mediators, drugs, and irritants on skin while avoiding the ethical concerns surrounding in vivo stimulation studies with non-approved agents. Nonetheless, few studies have utilized intact human tissue to study mast cell degranulation. This “Methods” paper describes the development and application of an intact skin explant model to study human mast cell activation. In this manuscript, we share our protocol for setting up ex vivo human skin explants and describe the results of stimulation experiments and techniques to minimize trauma-induced histamine release. Skin explants were generated using de-identified, full-thickness, non-diseased skin specimens from plastic and reconstructive surgeries. Results were reproducible and demonstrated FcɛRI- and MRGPRX2-induced mediator release which was inhibited with the use of a BTK inhibitor and QWF, respectively. Thus, this explant model provides a quick and accessible method of assessing human skin mast cell activation and inhibition.